Optimasi Penentuan Rute Terpendek Pengambilan Sampah Menggunakan Multi Travelling Salesman Problem - Ryan Mahaputra Krishnanda; Budi Darma Setiawan; Marji Marji (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Garbage is an unending environmental problem and this issue needs to be considered and handled together. According to data of 2015 from the Satuan Kerja Perangkat Daerah (SKPD) or Regional Device Work Unit of Denpasar, the annual garbage production in Denpasar is 1,335,819.48 m3. In the same year, the volume of garbage transport from the Department of Hygiene and Gardening or also known as Dinas Kebersihan dan Pertamanan (DKP) reached 1,065,016 m3 or realized 79.73% and shows the DKP transport fleet Denpasar can not touch the 80% target. This study will determine the optimal route for some garbage transport vehicles from the DKP office to the dump points and end up in the landfill. This happens because of the problem from Multi Traveling Salesman Problem (m-TSP) and one of the algorithms to solve m-TSP problems is with genetic algorithm. The process of this genetic algorithm uses permutation representation, crossover reproduction process with one-cut point, mutation process with exchange mutation, and selection process with elitism selection. After conducting the experiment, the most optimal parameter is obtained in population with the amount of 100, with the number of garbage transport vehicles as much as 4, the value of cr = 0.3, mr = 0.7 and the generation of 900. The results of the program with the parameters will yield 0.569 as maximum average of fitness value.